Role of toll-like receptor 10 gene polymorphism and gastric mucosal pattern in patients with chronic gastritis - Tongtawee, Taweesak; Bartpho, Theeraya; Wattanawongdon, Wareeporn; Dechsukhum, Chavaboon; Leeanansaksiri, Wilairat; Matrakool, Likit; Panpimanmas, Sukij (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Helicobacter pylori stimulates the host’s toll-like receptors (TLRs). Single-nucleotide polymorphism (SNP) of TLRs is related to the manipulation of regulatory cytokines and also implicated in the varied outcomes of the inflammatory response, including the development of precancerous lesions of gastric mucosa and disease progression. We hypothesized that TLR10 rs10004195 polymorphism is associated with gastric mucosal patterns. Materials and Methods: TLR10 rs10004195 polymorphisms were identified in a total of 400 gastritis patients using the TagMan SNP genotyping assay. Gastric mucosal patterns were classified by Conventional Narrow Band Imaging gastroscopy (C-NBI gastroscopy). Logistic regression was used to analyze the association. Results: The gastritis patients was Type 1, 37.5% of Thai patients. The T/T homozygous genotype was exhibited by the highest percentage (46.5%) of patients, and the A/A homozygous and A/T heterozygous genotypes were exhibited by 20.25% and 33.25%, respectively, of patients. TLR10 rs10004195 was significantly associated with gastric mucosal patterns. After adjusting for confounding factors, patients with the A/A homozygous genotype showed a significantly increased risk of severe inflammation (OR=1.35, 95% CI=0.97-2.13, p=0.028). Patients with the A/T heterozygous and T/T homozygous genotypes showed a significantly increased risk of mild inflammation (OR=1.24, 95% CI=0.78-2.07, p=0.042 and OR=1.78, 95% CI=0.51-3.35, p=0.001, respectively). Conclusion: Our results indicate that the presence of TLR10 rs10004195, A/T heterozygous, and T/T homozygous genotypes is associated with type 1, 2, and 3 whereas that of the A/A homozygous genotype is associated with type 4 and 5 of gastric mucosal patterns. This suggests that the A/A homozygous genotype contributes to severe inflammation in H. pylori-associated gastritis in Thai patients. Cite this article as: Tongtawee T, Bartpho T, Wattanawongdon W, et al. Role of toll-like receptor 10 gene polymorphism and gastric mucosal pattern in patients with chronic gastritis. Turk J Gastroenterol 2017; 28: 243-7.